2020
DOI: 10.3389/fphar.2020.00743
|View full text |Cite
|
Sign up to set email alerts
|

Postretrieval Microinjection of Baclofen Into the Agranular Insular Cortex Inhibits Morphine-Induced CPP by Disrupting Reconsolidation

Abstract: Environmental cues associated with drug abuse are powerful mediators of drug craving and relapse in substance-abuse disorders. Consequently, attenuating the strength of cuedrug memories could reduce the number of factors that cause drug craving and relapse. Interestingly, impairing cue-drug memory reconsolidation is a generally accepted strategy aimed at reducing the intensity of cues that trigger drug-seeking and drug-taking behaviors. In addition, the agranular insular cortex (AI) is an important component o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…Negative controls (without primary antibody) ensured secondary antibody specificity and pilot studies determined optimal primary antibody concentrations. Staining and expression was similar to previous studies (See Larson and Ariano, 1995 for DRD 2 ; Sun et al, 2020 for ΔFosB; and Threlfell et al, 2021 for DAT). For DRD 2 , antigen retrieval was performed prior to blocking.…”
Section: Methodssupporting
confidence: 83%
“…Negative controls (without primary antibody) ensured secondary antibody specificity and pilot studies determined optimal primary antibody concentrations. Staining and expression was similar to previous studies (See Larson and Ariano, 1995 for DRD 2 ; Sun et al, 2020 for ΔFosB; and Threlfell et al, 2021 for DAT). For DRD 2 , antigen retrieval was performed prior to blocking.…”
Section: Methodssupporting
confidence: 83%
“…Several studies have demonstrated that stroke-induced insula damage could lead to an abrupt and profound disruption of addiction to cigarette smoking without relapsing and craving ( 12 , 13 ), and patients in the insula lesion group quit heroin use entirely at a higher rate than controls ( 14 ). In addition, an array of recent studies using animal models and pharmacological or chemical interventions have showed that insula is involved in different aspects of addictive behavior of various addictive drugs ( 15 20 ). For example, morphine-induced conditioned place preference (CPP) in rats were attenuated in studies using administration of muscarinic acetylcholine receptor antagonists and nitric oxide inhibitors into insula ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…DAPT or vehicle was administered via bilateral intracranial microinjections at 0.5 μL/hemisphere. The GABA B receptor agonist baclofen (Sigma, USA) and the GABA B receptor antagonist phaclofen (Sigma, USA) were dissolved in saline and administered at doses of 0.06 nmol/0.2 μL/mouse [ 32 ] and 0.1 nmol /0.2 μL/ mouse [ 33 ], respectively.…”
Section: Methodsmentioning
confidence: 99%